Investigating Challenges of Individuals with Autism Spectrum Disorder During and Post COVID-19, and Practical Suggestions for Parents and Caregivers on How to Tackle Challenges: A Systematic Review Article - Nasiri, Amirpeyman; Entezari, Fatemeh; Karimi, Maryam; Naghibi, Narges; Golshan, Faly; Sabzalizadeh, Mansoureh; Afarinesh, Mohammad Reza (Current Psychiatry Research and Reviews, 2026)
IntroductionThe first and second waves of COVID-19 were unprecedented situations that caused turmoil in everyone’s life, especially for individuals with autism spectrum disorder (ASD) who were severely affected by the transition.ObjectiveThis article investigates the major impacts of COVID-19 transitioning on individuals in the spectrum followed by recommendations for autistic families on addressing concerns caused by post-COVID adaptations. We have based our study on the most recent investigations of challenges and solutions provided for these individuals in COVID and post-COVID-19 transitions. We will also explain telehealth as the most practical available solution and describe its possible advantages and disadvantages. The articles have been selected from PubMed, Google Scholar, etc. according to the goals stated above.ResultsAccording to our study, psychological problems, economic problems, reduced physical activity, sleep disorders, malnutrition, non-cooperation of children with ASD, and speech therapy were the most important challenges for people with ASD as well as their families and caregivers during the COVID-19 pandemic.ConclusionIt was concluded the use of telehealth could be a suitable platform for many educational methods such as applied behavior analysis, visual programs, speech therapy, family positive reinforcement systems, etc. to overcome these challenges. However, this method also has certain limitations, and therefore a combination of face-to-face and telehealth methods is recommended to help patients.
Keywords: caregivers; psychological problems